2010
DOI: 10.1189/jlb.0110001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory properties of the PI3K pathway are mediated by IL-10/DUSP regulation

Abstract: Resolution of inflammation is an important hallmark in the course of infectious diseases. Dysregulated inflammatory responses may have detrimental consequences for the affected organism. Therefore, tight regulation of inflammation is indispensable. Among numerous modulatory signaling pathways, the PI3K/PTEN signaling pathway has been proposed recently to be involved in the regulation of innate immune reactions. Here, we attempted to elucidate molecular mechanisms that contribute to the modulatory properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 36 publications
(77 reference statements)
2
44
0
Order By: Relevance
“…It has been shown that both wortmannin and LY294002 block in vitro phosphorylation of AKT by rictor-TORC2 kinase in addition to an inhibitory effect on PI3K (4,50). AKT activation appears to be important in immune tolerance through negative regulation of TLR pathways (51)(52)(53). This is further supported by the findings that MKP-1 induction in response to heat-killed Acinetobacter baumannii is augmented by PTEN deficiency but attenuated by PI3K deficiency (52).…”
Section: Discussionmentioning
confidence: 84%
“…It has been shown that both wortmannin and LY294002 block in vitro phosphorylation of AKT by rictor-TORC2 kinase in addition to an inhibitory effect on PI3K (4,50). AKT activation appears to be important in immune tolerance through negative regulation of TLR pathways (51)(52)(53). This is further supported by the findings that MKP-1 induction in response to heat-killed Acinetobacter baumannii is augmented by PTEN deficiency but attenuated by PI3K deficiency (52).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, it has been shown that the PI3K signalling suppresses TLR-induced p38 phosphorylation in innate immune cells including DCs [37] and macrophages [38]. Enhanced activity of PI3K in macrophages results in increased DUSP1 (a p38 specific phosphatase) expression, IL-10 production and, as a result, diminished p38 activation and lowered production of proinflammatory cytokines in response to pathogens [39].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a protein that acts as a tumor suppressor, and is a negative regulator of inflammation. Correspondingly, in PTEN-knockdown cells, expression of the immunomodulatory factor (IL-10) was found to decrease [8], and expression of the pro-inflammatory factor, TNF-a markedly increased [14][15]. In the present study, following a coronary interventional procedure, PTEN mRNA and protein produced by CD4+ T lymphocytes were found to be down-regulated, and serum levels of TNF-a were also significantly elevated.…”
Section: Discussionmentioning
confidence: 62%
“…Phosphatase and tension homolog deleted on chromosome ten (PTEN) has been identified as a tumor-suppressor gene and has been associated with maintaining the balance between cell survival and cell death, and which has been shown to inhibit an inflammatory response. Gunzl et al reported that PTEN-deficient immunocytes increase inflammatory cytokine production, and reduce anti-inflammatory cytokine IL-10 production [8]. In addition, our preliminary experiment identified a significant decrease in PTEN expression by CD4+ T lymphocytes in patients undergoing PCI compared with controls.…”
Section: Introductionmentioning
confidence: 49%